Little monsters : a novel - Brodeur, Adrienne (New York, NY : Avid Reader Press, 2023)
Ken and Abby Gardner lost their mother when they were small and they have been haunted by her absence ever since. Their father, Adam, a brilliant oceanographer, raised them mostly on his own in his remote home on Cape Cod, where the attachment between Ken and Abby deepened into something complicated-and as adults their relationship is strained. Now, years later, the siblings' lives are still deeply entwined. Set in the fraught summer of 2016, and drawing on the biblical tale of Cain and Abel, Little Monsters is an absorbing, sharply observed family story by a writer who knows Cape Cod inside and out-its Edenic lushness and its snakes. --
Keywords: Siblings -- Fiction; Sibling rivalry -- Fiction; Fathers -- Fiction; Families -- Fiction; People with bipolar disorder -- Fiction; Psychic trauma -- Fiction; Cape Cod Bay (Mass.) -- Fiction; Domestic fiction